New worlds and the Italian renaissance : contributions to the history of European intellectual culture - Moudarres, Andrea; Moudarres, Christiana Purdy (Brill's studies in intellectual history., 2012)
This volume seeks to gauge the import of the Italian Renaissance in shaping the foundations of what we conventionally define as 'modernity.' The authors engage in an interpretative conversation with historians and thinkers such as Jacob Burckardt, Ernst Cassirer, Martin Heidegger, Eugenio Garin, and Louis Dupré, whose works have oriented the search for the roots of modernity and for the significance of Renaissance Humanism. The studies presented in this collection contribute to this effort from various perspectives: scientific, theological, political, and literary. The result is amultifaceted illumination of the intellectual history of the Italian Renaissance.